A flexible self-adaptive seal concept for sealing performance enhancement by controlling the flow contraction effect - Weirong Wu; Qianlei Gu; Wanfu Zhang; Hongyu Gao; Yucong Zhang; Mingjie Zhang (Ain Shams Engineering Journal, 2025)
Annular gas seals are critical components in turbomachines for restricting leakage and ensuring efficiency. Reducing seal clearance is the most direct method to minimize leakage. Flexible seals such as brush seals, leaf seals, and finger seals are typical solutions. These seals achieve minimal leakage rates through extremely tight clearances, yet face inevitable rubbing risk during severe operational conditions. This paper proposes a novel flexible self-adaptive seal (FSS), featuring axial flexible teeth and radial rigid teeth. The radial deformation of flexible teeth, induced by the natural pressure differential between the outer and inner surface, enables adaptive clearance adjustment. With this effect, the inherent rub problem in traditional flexible seals is resolved. A two-way fluid–structure interaction (FSI) analysis was carried out, simulating the deformation characteristics and the flow field distribution for various operating conditions and flexible teeth geometric parameters. Results indicate that when leakage fluid passes through the seal clearance, a flow contraction effect occurs. This effect creates a low-pressure zone on the inner surface of the flexible teeth, while the outer surface exists higher cavity pressure. Under the pressure differential between the two surfaces, the flexible teeth deform toward the rotor center, enabling adaptive clearance adjustment. This effect contributes to the enhanced flow contraction, thus increasing the leakage resistance. The leakage reduction effect of FSS increases as the pressure ratios (PR) increase. For the case of PR = 9.9, the maximum leakage reduction ratio reaches 24 % compared to the traditional labyrinth seal. The proposed FSS offers critical advancements in sealing capability for high-parameter operational scenarios.